Bibliography of Hungarian dictionaries, 1410-1963 - Halasz de Beky, I. L., 1919- (University of Toronto Press, 1966)
This bibliography has been compiled with the aim of providing a useful tool for linguists, scientists, translators, and students of the Hungarian language. It covers a variety of subjects, from atomic physics to card games, from fifteenth-century Latin-Hungarian glossaries to twentieth-century underworld slang. No dictionary, even the most comprehensive, takes the place of a highly specialized subject dictionary. With the help of this bibliography, readers can find more easily a Hungarian dictionary for the language or subject they require.